The Role of Academic and Professional English Communication in Promoting Traditional Clothing Brands: Case Study of PJSC "Edelvika" - Mokhniuk, Anna; Sazhnieva, Anna (My University, 2025)
This article explores the role of academic and professional English communication in enhancing the visibility and competitiveness of traditional clothing brands, using the Ukrainian textile company PJSC “Edelvika” as a case study. The purpose of the article. The purpose of this article is to analyze how Edelvika uses English-language communication in its branding, marketing, and customer interaction strategies to reach international audiences, enhance its image, and facilitate cross-cultural engagement. The research also aims to assess the practical impact of English communication on the company's global competitiveness and brand positioning. Methods. To address the research questions, the study employed a mixed-methods approach. A qualitative analysis of Edelvika’s communication practices was conducted through a review of the website content, labelling, and promotional materials. In parallel, quantitative analysis was applied to financial and operational indicators over five years (2020–2024) to assess correlations between English communication strategies and business performance. Results. The results show that Edelvika uses the English language not only for delivering technical information and customer support but also as a strategic tool for communication culture values and product uniqueness. The content in English supports international sales, increases consumer trust and makes the brand more recognizable. Conclusions. Academic and professional English communication significantly contributes to the successful promotion of traditional clothing brands in global markets. In the case of Edelvika, English facilitates the transmission of cultural identity in a professional format, making the brand more competitive and recognizable internationally.
Keywords: academic communication; professional communication; cross-cultural marketing; traditional clothing; branding; international promotion; textile industry; cultural identity; global competitiveness; 005.336.4:658.8:81'243